2014
DOI: 10.1002/ajh.23745
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, outcome, and prognostic factors for survival and evolution to multiple myeloma of solitary plasmacytomas: A report of the Greek myeloma study group in 97 patients

Abstract: Solitary plasmacytoma (SP) is a rare plasma cell dyscrasia characterized by the presence of bone or extramedullary plasma cell tumors. The treatment of choice is local radiotherapy (R/T) 6 surgical excision. The role of adjuvant chemotherapy (C/T) or novel agents (NA) is uncertain. Data related to prognostic factors are inconclusive. Herein, we describe the clinical features, survival and prognosis of 97 consecutive patients, 65 with bone SP (SBP), and 32 with extramedullary SP (SEP), diagnosed and treated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 33 publications
5
42
1
Order By: Relevance
“…Katodritou et al reported outcome of 65 SBP and 32 SEP patients treated in 12 different Greek centers with a median follow‐up of 5 years. Unlike our study, 48% of their patients received chemotherapy alone or combined with radiotherapy . The overall 5‐ and 10‐year OS, PFS and MMFS were comparable to what we found.…”
Section: Discussionsupporting
confidence: 71%
“…Katodritou et al reported outcome of 65 SBP and 32 SEP patients treated in 12 different Greek centers with a median follow‐up of 5 years. Unlike our study, 48% of their patients received chemotherapy alone or combined with radiotherapy . The overall 5‐ and 10‐year OS, PFS and MMFS were comparable to what we found.…”
Section: Discussionsupporting
confidence: 71%
“…Reported by Huang et al, in patients with SP of cervical spine, adjunctive RT following excision obviously decreased MM progression (Huang et al, 2010). Another retrospective study showed favorable effects related to melphalan-based chemotherapy in preventing MM development (Mayr et al, 1990), but others didn't report any benefits of chemotherapy (Holland et al, 1992;Katodritou et al, 2014). Unfortunately, our study doesn't have the potency to explore the effectiveness of intensive therapy in patients of high risk owing to the small number of events.…”
Section: Discussionmentioning
confidence: 86%
“…There are no data available from randomized clinical trials to guide therapy in SBP and EMP. Local radiotherapy is the recommended treatment for SBP while EMP often can be treated by surgery with or without radiotherapy . Available data do not support the use of adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%